Hydrodynamic characteristics of blowing and suction on sheet-cavitating flows around hydrofoils. (1st March 2016) - Akbarzadeh, Pooria; Akbarzadeh, Ebrahim
Abstract: In this study the effect of blowing and suction on hydrodynamic behavior of sheet-cavitating flows over hydrofoils is investigated. A computational program is developed for simulation of inviscid cavitating flows. In this simulation, the Jameson׳s finite volume technique and the progressive power-law preconditioning method for analyzing the cavitating flows are utilized. For cavitation modeling the barotropic cavitation pattern is used. The numerical stabilization is achieved via the second and fourth-order dissipation terms. Explicit four-step Runge–Kutta time integration is applied to achieve the steady-state condition. Cavitating flows over NACA-hydrofoils for different cavitation numbers are investigated. To apply the blowing and suction, a jet is placed on the hydrofoil׳s upper surface. Four blowing (and suction) parameters i.e., velocity ratio, jet location, width of jet, and jet angle are scrutinized. The effects of these parameters on surface pressure distribution, length of cavitation, lift and pressure drag coefficients are examined. The results indicate that blowing jets often decrease the length of cavity and reduce the lift and pressure drag coefficients, while suction jets behave reversely. Also, by increasing the blowing amplitude or the width of jet, the lift and pressure drag coefficients and the length of cavity decrease while in suction cases, they increase. Highlights: Effects of blowing/suction on behavior of sheet-cavitating flows are investigated. Power-law preconditioning method for analyzing the cavitating flows is utilized. Effects of velocity, location, width, and angle of blowing/suction are scrutinized.